Integrated analysis of transcriptomics and metabolomics of peach under cold stress - Li, Yonghong; Tian, Qihang; Wang, Zhaoyuan; Li, Jie; Liu, Shiyuan; Chang, Ruifeng; Chen, Hu; Liu, Guojian (Frontiers in Plant Science, 2023)
Low temperature is one of the environmental factors that restrict the growth and geographical distribution of peach (Prunus persica L. Batsch). To explore the molecular mechanisms of peach brunches in response to cold, we analyzed the metabolomics and transcriptomics of ‘Donghe No.1’ (cold-tolerant, CT) and ‘21st Century’ (cold-sensitive, CS) treated by different temperatures (-5 to -30 °C) for 12 h. Some cold-responsive metabolites (e.g., saccharides, phenolic acids and flavones) were identified with upregulation only in CT. Further, we identified 1991 cold tolerance associated genes in these samples and they were significantly enriched in the pathways of ‘galactose metabolism’, ‘phenylpropanoid biosynthesis’ and ‘flavonoids biosynthesis’. Weighted gene correlation network analysis showed that soluble sugar, flavone, and lignin biosynthetic associated genes might play a key role in the cold tolerance of peach. In addition, several key genes (e.g., COMT, CCR, CAD, PER and F3’H) were substantially expressed more in CT than CS under cold stress, indicating that they might be major factors during the adaptation of peach to low temperature. This study will not only improve our understanding towards the molecular mechanisms of peach trees under cold stress but also contribute to the screening and breeding program of peach in the future.